Integration of PjBL-STEM and Virtual Laboratory as a Strategy to Enhance 21st Century Scientific Literacy in Junior High School Science Learning - Saputra, Ahmad; Fandi, Real; Nurohman, Sabar; Natadiwijaya, Ismail Fikri; Wilujeng, Insih; Widowati, Asri; Damayanti, Herlina (IJIS Edu : Indonesian Journal of Integrated Science Education, 2026)
This study aims to analyze the effectiveness of integrating Project-Based Learning (PjBL) with Science, Technology, Engineering, and Mathematics (STEM) and virtual laboratories in enhancing 21st-century scientific literacy among junior high school students. A quasi-experimental design employing a one-group pretest–posttest model was used, involving 25 seventh-grade students from SMP Negeri 11 Yogyakarta. Data were collected using a scientific literacy test encompassing three dimensions: explaining phenomena scientifically, interpreting data and scientific evidence, and evaluating and using scientific information. The results revealed a significant difference between pretest and posttest scores (p < 0.05), with a normalized gain score of 0.62 categorized as medium. The greatest improvement occurred in the dimension of explaining phenomena scientifically (0.83), followed by interpreting data and scientific evidence (0.67), and evaluating and using scientific information (0.58). The integration of PjBL-STEM with virtual laboratories enhanced students’ conceptual understanding, scientific reasoning, and inquiry skills through interactive and contextual learning experiences. These findings demonstrate that the hybrid PjBL-STEM model, supported by virtual laboratory simulations, effectively promotes 21st-century scientific literacy. Moreover, this study provides empirical evidence on how the integration of PjBL-STEM and virtual laboratories can bridge the gap in scientific literacy development within Indonesian secondary education.